INFLUENCE OF SOCIAL MEDIA COMMERCE AND FINANCIAL MANAGEMENT SKILLS ON STUDENT CONSUMPTION PATTERNS: EVIDENCE FROM INDONESIAN HIGHER EDUCATION - Eka Putri Nur Wahyuni; Moh Usman Kurniawan; Arie Eko Cahyono (CV. TOTUS TUUS, 2025)
The rapid integration of social media platforms—particularly TikTok and its e-commerce feature, TikTokShop—has significantly shaped the consumption patterns of university students, fostering both new opportunities and financial challenges. This study aims to analyze the partial and simultaneous effects of TikTokShop usage and financial management ability on the consumptive behavior of first-year students at Universitas PGRI Argopuro Jember. Employing a quantitative, cross-sectional survey design, data were collected from 95 purposively selected students using validated questionnaires, with analysis conducted via multiple linear regression. The results indicate that while financial management ability has a significant positive effect on consumptive behavior (p < 0.05), TikTokShop usage does not have a significant direct impact. Nonetheless, when combined, both variables account for nearly 70% of the variance in consumptive behavior, underscoring the crucial moderating role of financial management skills in the digital consumption context. The findings highlight that developing financial competence is more effective in promoting responsible spending than merely limiting digital platform use. This research contributes to the literature by isolating TikTokShop as a unique influence and emphasizing applied financial skills over general literacy. The study's practical value lies in its recommendations for higher education to integrate targeted financial management programs within curricula. Future research should examine additional moderating variables such as peer influence and socioeconomic status, and extend the analysis to diverse institutional and demographic contexts.